2011
DOI: 10.1097/mjt.0b013e3181bc0f5a
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonemergent Percutaneous Coronary Intervention With and Without On-site Surgical Backup: A Meta-Analysis

Abstract: Despite major advances in percutaneous coronary intervention (PCI) techniques, the current guidelines recommend against elective PCI at hospitals without on-site cardiac surgery backup. Nonetheless, an increasing number of hospitals without on-site cardiac surgery in the United States have developed programs for elective PCI. Studies evaluating outcome in this setting have yielded mixed results, leaving the question unanswered. Hence, a meta-analysis comparing outcomes of nonemergent PCI in hospitals with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…[1][2][3][4][5] Observational studies exploring the safety of PCI facilities without on-site CT surgery have generally supported these trial findings. [6][7][8][9][10] As a result, current PCI guidelines allow for the procedure at facilities without on-site CT surgery, but call for appropriate program development and quality oversight.…”
mentioning
confidence: 51%
“…[1][2][3][4][5] Observational studies exploring the safety of PCI facilities without on-site CT surgery have generally supported these trial findings. [6][7][8][9][10] As a result, current PCI guidelines allow for the procedure at facilities without on-site CT surgery, but call for appropriate program development and quality oversight.…”
mentioning
confidence: 51%
“…9,[11][12][13][14][15][16][17][18][19][20][21][22][23] Primary PCI without on-site surgery Seven studies and 2 meta-analyses of primary PCI showed no difference for in-hospital or 30-day mortality between sites with and without on-site surgery ( Table 1). None of the individual studies examining the occurrence of emergency CABG surgery after primary PCI showed a difference between sites with and without on-site surgery.…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
“…Three meta-analyses conducted primarily with registry data have examined the use of nonprimary PCI at facilities with and without on-site surgery [19,20,23]. Overall, the mortality rate and need for emergency CABG surgery did not differ between hospitals with and without on-site surgery.…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%
“…Since 2006, 11 original studies and 3 meta-analyses on the topic of PCI without on-site surgery have been identified by a computerized systematic literature search using Medline (PubMed and Ovid) and Cochrane Databases [9,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Recent Literature On Pci Without On-site Surgerymentioning
confidence: 99%